A heuristic framework for voice instruction at the doctoral level - Olivier, Alet; Carstens, Adelia (Stellenbosch Papers in Linguistics Plus, 2018)
The notion of voice as an integral aspect of language use has been extensively theorised in linguistics. However, empirical research and pedagogical models have not yet matched the sophistication of voice theories in linguistics, and little attention has been paid to advanced academic writing. This article attempts to address two pertinent gaps in the pedagogical and empirical literature: inadequate training of doctoral students to make an authentic contribution to knowledge creation in their respective fields, of which a distinctive authorial voice is a criterial feature; and bridging the gap between theory-and practice. An account is given of two theoretical models of voice â€“ both embedded in Systemic Functional Linguistics â€“ that have served as the basis of the majority of instruments aimed at concretising the somewhat elusive notion of voice. An overview is given of existing heuristics of voice designed by other scholars, followed by the presentation and description of a self-developed and comprehensive heuristic framework for voice that may inform the development of instructional toolkits for doctoral students.Â